060 Appraising Implementability During the Development Process Resulted in Guideline Revision. (15th August 2013) - Veer, S van der; Simon, A; Weismann, D; Lehner, G; Coentrão, L; Dongelmans, D; Laecke, S van; Lapauw, B; Ortiz, A; Schiller, A; Tesar, V; Nagler, E
Abstract : Background: The GuideLine Implementability Appraisal (GLIA) instrument has been suggested for identifying potentially remediable implementability issues during the guideline development process. Objective: To explore to what extent using GLIA during the development process would result in guideline revision before publication. Methods: The development process of the European hyponatremia guideline -coordinated by European Renal Best Practice - was our study context. Using the GLIA web-tool, eleven clinicians and methodologists from eight countries individually appraised 27 guideline statements. In a face-to-face consensus meeting, four GLIA panelists and one guideline development group (GDG) representative summarised potential implementability issues. The GDG discussed these issues, and revised the guideline if deemed necessary. Results: We identified 33 issues; the GDG accepted 26 as potentially hampering implementability. This resulted in statement reformulation with (n=5) and without (n=10) influencing clinical content, adding or (re)moving entire statements (n=8), and adding information to tables or rationales (n=3). The majority of issues declined by the GDG (n=7) addressed clinical situations that were covered elsewhere in the guideline or were considered to be uncommon. Discussion: Using GLIA during the development process resulted in a revised guideline. We felt that GDG representation in the consensus meeting optimize our appraisal process. Implications for Guideline Developers/Users: Guideline organizations may want to consider incorporating GLIA into their development process. This may raise GDGs' awareness of potential implementability issues, and allow revision of the guideline accordingly prior to publication. Future research should explore the effect of GLIA-based revisions on implementability as assessed by guideline users.